The impact of the fourth industrial revolution on the formation of metal Jewelry in the light of fractal geometry (Al-Academy, 2024)
The advanced technologies of the Fourth Industrial Revolution with its great impact on various industrial aspects came with the emergence of the term "the Fourth Industrial Revolution, as a result of the continuous technological developments that addressed many modern technologies such as additive manufacturing and augmented reality, that significantly contributed to the development of metal jewelry formation in light of molecular engineering, as the design and manufacture of metal jewelry using molecular engineering required modern and advanced technology for the ability to design and ease of implementation.Applications of the Fourth Industrial Revolution have rapidly emerged in the design of metal jewelry through 3D printing, which was used in the formation of precious metals, and with the variety of jewelry designs and shapes that require time and effort for implementation, especially if there is a need to create special or valuable pieces or to reproduce rare pieces. Therefore, it was important to study the impact of the Fourth Industrial Revolution, the changes it brought about, and how to benefit from the advanced technologies for forming metal jewelry in light of molecular engineering. To facilitate the implementation of interwoven and complex shapes and designs inspired by molecular engineering.The research deals with the Fourth Industrial Revolution, its concept, and principles, how it appeared, and the various technologies that emerged with it, as well as its various effects, in addition to the methods of forming metal jewelry and its development from manual and traditional methods to modern and advanced methods. It also deals with molecular engineering and how to benefit from it in forming and implementing metal jewelry through the technologies of the Fourth Industrial Revolution to achieve the research goal.